The Origins of Kuwait - Slot, B.J., (Middle East and Islamic Studies - Book Archive pre-2000., 1991)
Since the discovery of the worlds third largest oil reserves within its borders, Kuwait has achieved international political prominence far exceeding its physical size. The country had already played a role in history before, however. Local sources take that history back to the beginning of the nineteenth century. The present book takes the history of Kuwait still further back using European sources. It includes analyses and comparisons of indications on maps from the sixteenth century onwards and of references to the Kuwait area in documents produced by officials of the Dutch East India Company-the principal Western political and economic power in the Gulf during most of early modern times-, in British documents and in early travel accounts. The book is a valuable contribution to our knowledge of the political position of Kuwait in history vis-à-vis its neighbours, especially the Ottoman authorities in Basra.